CO2 capture by a novel CaO/MgO sorbent fabricated from industrial waste and dolomite under calcium looping conditions. (11th March 2019) - Yan, Xianyao; Li, Yingjie; Ma, Xiaotong; Zhao, Jianli; Wang, Zeyan; Liu, Hantao
Abstract : A synthetic sorbent prepared from carbide slag and dolomite by combustion exhibits high CO2 capture capacity, good cyclic stability and a porous microstructure. Abstract : Herein, the novel CaO/MgO CO2 sorbent was fabricated from carbide slag and dolomite by the combustion method during the calcium looping process. The carbide slag is a precursor of CaO, and dolomite is a precursor of both MgO and CaO. The effects of the mass ratio of the carbide slag to dolomite, calcination conditions and presence of steam during carbonation on the CO2 capture performance of the novel CaO/MgO sorbent were studied during the calcium looping cycles. When the mass ratio of the carbide slag to dolomite was 74 : 26, the resulting CaO/MgO sorbent having the mass ratio of CaO to MgO = 90 : 10 achieved highest CO2 capture capacity that was retained at 0.52 g g −1 after 20 cycles (carbonation in 15% CO2 /85% N2 at 700 °C for 20 min; calcination in 100% N2 at 850 °C for 10 min), which was higher than those of the carbide slag and other reported CaO/MgO sorbents prepared from analytical reagents. Compared with that of the sample calcined under pure CO2 at 950 °C, the CO2 capture capacity of the CaO/MgO sorbent calcined in pure steam at 800 °C is apparently higher. This novel CaO/MgO sorbent fabricated from industrial waste and dolomite exhibits a more porous microstructure, which is promising for the calcium looping process for CO2 capture.